Can Trait-Based Schemes Be Used to Select Species in Urban Forestry? - Watkins, Harry; Hirons, Andrew; Sjöman, Henrik; Cameron, Ross; Hitchmough, James D. (Frontiers in Sustainable Cities, 2021)
Urban forests in northern Europe are threatened by climate change and biosecurity risks, and in response, city planners are urged to select a wider portfolio of tree species to mitigate the risks of species die-off. However, selecting the right species is a challenge, as most guidance available to specifiers focuses on ecosystem service delivery rather than the information most critical to tree establishment: the ability of a species to tolerate the stresses found in a given place. In this paper, we investigate the potential of using ecological techniques to describe ecological traits at the level of species selection, and the potential of functional ecology theories to identify species that are not widely discussed or specified at present but might be suitable. We collected trait data on 167 tree species across 37 genera, including 38 species within a case study genus, Magnolia L., and tested four theories that posit ways in which traits trade off against each other in predictable ways. We found that at this scale, most species recommended for urban forestry tend to be ordinated along an axis of variation describing pace of life and stress tolerance, and that most Magnolia species are described as being fast-growing rather than stress-tolerant, although there is a degree of inter-specific variation. Further, we found that only one theory offers a succinct and reliable way of describing physiological strategies but translating ecological theory into a form appropriate for urban forestry will require further work.